Analisis Persepsi Nasabah Konversi Bank Nagari Konvensional menjadi Bank Nagari Syariah: (Studi Kasus pada Bank Nagari Cabang Bukittinggi) - Nasfi, Nasfi; Dewi, Sandra; Sabri, Sabri (JUSIE (Jurnal Sosial dan Ilmu Ekonomi), 2020)
The purpose of this study is to determine and analyze customer perceptions about the conversion of conventional Nagari Bank to Islamic Nagari Bank, as well as to analyze the obstacles that occur when conventional Nagari Bank converts to Bank Nagari Syariah. The research method is field research (field research), data collection techniques using observation, in-depth interviews and documentation and data analysis techniques using qualitative descriptive analysis methods. The results showed that the dominant perceptions of Bank Nagari customers supported and loyal to the decision of Bank Nagari to convert to Sharia so that they could apply the Minangkabau philosophy. Meanwhile, the obstacles faced by Bank Nagari are from the internal side such as the readiness of human resources, the era of digitalization or the digital ecosystem and it is not easy to provide products that have significant changes, from the external side such as the spread of the corona virus, the impact of the trade war between the United States and China and different views from Public.